Eclair and present danger - Bradford, Laura (Bradford, Laura. Emergency Dessert Squad mysteries., 2016)
"With her rent rising, Winnie Johnson had hoped her bakery would be saved by an inheritance from her wealthy friend and neighbor Gertrude Redenbacher. Instead she gets the widow's hostile tabby, Lovey, and a vintage ambulance restored by Gertrude's late husband. As Winnie's dream crumbles, she delivers a peach pie to an elderly widower and finds him smothered by a pillow. Winnie comes to the rescue of her frightened and grieving neighbors with baked goods -- and an idea is born: dessert delivery via her ambulance and a new business called the Emergency Dessert Squad. When she's not speeding to the scenes of dessert emergencies, Winnie is also racing to track down Bart's killer -- before she needs to call a real ambulance for the next victim..."--